2012
DOI: 10.7162/s1809-97772012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and deglutition after total laryngectomy

Abstract: Summary Introduction: Total laryngectomy creates deglutition disorders and causes a decrease in quality of life Aim: To describe the impact of swallowing and quality of life of patients after total laryngectomy. Method: A case series study. Patients completed a Swallowing and Quality of Life questionnaire composed of 44 questions assessing 11 domains related to quality of life (burden, eating duration, eating desire, frequency of symptoms, food selection, communication, fear, mental health, social functioning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Although patients expect and adapt to some diminution in levels of swallowing functioning after such significant surgery, Maclean et al found long-term self-reported swallowing problems in 72% of patients after TL [12]. Patients reported complaints about food sticking in the throat, regurgitation, increased swallow attempts, tightness, and prolonged mealtimes [13,14]. These complaints can be attributed to the altered anatomy and physiology of the neopharynx.…”
Section: Introductionmentioning
confidence: 99%
“…Although patients expect and adapt to some diminution in levels of swallowing functioning after such significant surgery, Maclean et al found long-term self-reported swallowing problems in 72% of patients after TL [12]. Patients reported complaints about food sticking in the throat, regurgitation, increased swallow attempts, tightness, and prolonged mealtimes [13,14]. These complaints can be attributed to the altered anatomy and physiology of the neopharynx.…”
Section: Introductionmentioning
confidence: 99%